A Modified Boronic Acid (MBA) Disc Potentiation Assay for Detection of Extended Spectrum ?-Lactamase (ESBL) Producing Bacteria - Naeem, Nazratan; Sultana, Munawar; Hossain, M Anwar (Bangladesh Journal of Microbiology, 2016)
In this study, a modified boronic acid (MBA) disc potentiation assay has been used to detect extended spectrum â-lactamase (ESBL) producing isolates from clinical liquid waste (CLW) in Bangladesh. The method is modified from the existing boronic acid (BA) disc potentiation assay in that, in our protocol only one type of antibiotic disc is required in comparison to the requirement of different types of antibiotic discs for the BA test. Clavulanic acid (CA) and Boronic acid (BA) were used to phenotypically identify ESBL and AmpC producers, respectively. A total of 181 multidrug-resistant (MDR) isolates were screened for ESBL production by both the conventional double disc diffusion synergy test (DDST) and the MBA disc potentiation test. Among these two methods, 38% of the isolates showed positive ESBL phenotype in MBA test in comparison to the 24% of the isolates in DDST, hence showed higher efficiency. The MBA method described here is efficient, easy to perform, and cost effective to detect ESBL producing bacteria. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 29-33